Underlying Cause of Out‐of‐Hospital Cardiac Arrests in Japan in Survivors Versus Nonsurvivors - Satoshi Yoshimura; Zian H. Tseng; Tomoki Yamada; Shunichiro Nakao; Kazuhisa Yoshiya; Changhwi Park; Tetsuro Nishimura; Takuya Ishibe; Kazuma Yamakawa; Takeyuki Kiguchi; Masafumi Kishimoto; Kohei Ninomiya; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The causes underlying out‐of‐hospital cardiac arrest (OHCA) are rarely investigated. This study aimed to investigate causes of OHCA in CRITICAL (Comprehensive Registry of In‐Hospital Intensive Care for OHCA Survival), a multicenter OHCA registry in Osaka, Japan. Methods Nontraumatic patients with OHCA (by CARES [Cardiac Arrest Registry to Enhance Survival] criteria) aged 18 to 90 years between July 1, 2012 and December 31, 2020 were included. By Japanese law, all patients with OHCA (resuscitated or not) must be transported to the emergency department where death is declared if resuscitation is unsuccessful; this latter group was considered presumed sudden cardiac deaths whereas those surviving to hospitalization were considered resuscitated OHCA. We compared underlying causes of OHCA in presumed sudden cardiac deaths, survivors of OHCA (alive 30 days after the event), and nonsurvivors of OHCA (died during hospitalization). Causes were confirmed when autopsy or postresuscitation hospital workup was performed and probable when determined by attending physician impression (partial workup). Results Of 12 252 total OHCAs, 8005 (65.3%) were. presumed sudden cardiac deaths, 4247 (34.7%) were resuscitated, and 1293 (10.6%) were survivors. Resuscitated OHCA cardiac causes comprised 73.2% (n=3110) and noncardiac causes 26.8% (n=1137). Cardiac cause, most commonly acute coronary syndrome, was more prevalent in survivors of OHCA than nonsurvivors (85.7% [n=1137] versus 67.8% [n=2002]; P<0.001). Although 40.4% of the survived at 30 days cases were acute coronary syndrome, cerebrovascular disease accounted for 9.8% of nonsurvivors of OHCA and nearly one fifth (n=144, 17.8%) of middle‐aged cases. Conclusions Cardiac cause was more common in survivors than cases dying in the emergency room (sudden deaths) or in hospital after initial resuscitation (nonsurvivors of OHCA). Causes in nonsurvivors of OHCA who died in hospital were more heterogeneous than those of survivors of OHCA, especially cerebrovascular emergencies.